1958
DOI: 10.1136/bjo.42.2.65
|View full text |Cite
|
Sign up to set email alerts
|

Vascularization of the Primary Optic Pathways

Abstract: FIRST we will study the macroscopic or extra-tissular, and afterwards the microscopic or intra-tissular vascularization of the primary optic pathways. The latter has been especially studied by microradiographic examination of sections 0O1-0-5 mm. thick after injecting Heyden's thorotrast. (A) MACROSCOPIC (EXTRA-TISSULAR) VASCULARIZATION OF THE PRIMARY OPTIC PATHWAYS The central retinal artery, though making use of the optic nerve to reach the retina, supplies only the latter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0
6

Year Published

1958
1958
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 2 publications
0
10
0
6
Order By: Relevance
“…The inferior bundle initially passes anteriorly to loop into the temporal lobe before passing posteriorly through the parietal lobe. The blood supply to the optic radiations is predominantly from the posterior and middle cerebral arteries [24]. The nerve fibres of the optic radiations terminate in the visual striate cortex (V1) which is located on the medial aspect of the occipital lobe, superior and inferior to the calcarine fissure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inferior bundle initially passes anteriorly to loop into the temporal lobe before passing posteriorly through the parietal lobe. The blood supply to the optic radiations is predominantly from the posterior and middle cerebral arteries [24]. The nerve fibres of the optic radiations terminate in the visual striate cortex (V1) which is located on the medial aspect of the occipital lobe, superior and inferior to the calcarine fissure.…”
Section: Introductionmentioning
confidence: 99%
“…A parieto-occipital branch supplies the superior calcarine lip, a posterior temporal branch supplies its inferior lip, and a calcarine branch supplies the central region posteriorly. The middle cerebral artery may supply the posterior aspect of the calcarine sulcus with an anastomosis between posterior and middle cerebral arteries accounting for sparing of the macula in cases of posterior cerebral artery occlusion [24, 25]. …”
Section: Introductionmentioning
confidence: 99%
“…The results of the authors who gave detailed descriptions of the existence of the central artery of the optic nerve showed that it proceeded to the retina. Nevertheless, they estimated that it did not participate in vascularization of the optic nerve [6]. The other groups of authors had doubts about the existence of this kind of vascular division.…”
Section: Discussionmentioning
confidence: 98%
“…The earliest descriptions have pointed out that pial arterial plexus vascularize optic nerve over its entire length [6]. This vascular scheme was completed with the indings of other researchers, who described more branches, 1-3, coming from the ophtalmic artery (OA), as it passed through the optic canal [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The visual field in this case demonstrates a predominantly scotomatous defect and, in the absence of any marked infero-nasal defect in the peripheral field which would correspond to the supero-lateral position of the tumour, the macular sensitivity is more readily explained on a vascular basis. It has been shown that there is no axial artery in the intracanalicular portion of the optic nerve, but that the blood supply is by a pre-capillary plexus, the distribution of which is irregular (Fran9ois, Neetens, and Collette, 1958). Thus the field changes in this case conform with those described in other cases of optic nerve compression (Traquair, 1946;Hughes, 1958), and there is evidence that the scotoma is extending peripherally, though the breakthrough is not occurring in the peripheral fibres directly related to the site of the tumour.…”
Section: Discussionmentioning
confidence: 99%